Cultural Locality and Bureaucracy on the Sukabumi City Police Command - Rycko Amelza Dahniel (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Rational bureaucratic models in various organizational contexts can no longer be implemented as originally designed because of the interaction of cultural locality, including in city-level police organizations. Services to the community in the District of Sukabumi cannot be implementedappropriately. It is because there are three problems, namely the absence of detailed and transparent rules, the lack of material and budget support, and the functional relationship between the police and the community, which is influenced by the dominant local culture. This research investigates the variety of features of cultural locality in the bureaucracy of Sukabumi ResortPolice through a qualitative approach.The source of research data is determined purposively and snowball based on an emic approach to get social phenomena that occur. Data mining is carried out in the form of complete participant observation, interviews, and document studies. The results of the research revealed that the bureaucracy in resort police is characterized by a unique hierarchical chain and unity of command through and carried out by superiors, specialization into functions, regulations and organizational policies, standard procedures for each job, career coaching structure, and impersonal relationships. In addition, the cultural context and locality of the Sukabumi community, which is thick with Sundanese culture, become a social convention which is manifested in activities, actions, and ways of thinking. These manifestations are based on friendship, mutual assistance and respect, respect for parents, deliberation in solving social problems that refer to the culture of diriungkeun by using religious figures, preachers, and ajengan as primordial charismatic figures.Cultural context and locality are believed to have influenced the bureaucratic style so that the rational bureaucracy cannot be fully implemented but must adopt local culture.